1996
DOI: 10.1074/jbc.271.50.31807
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Triple-stranded DNA at d(GA·TC) Sequences Prevents Nucleosome Assembly and Is Hindered by Nucleosomes

Abstract: Simple repeating d(GA⅐TC)n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…The selection between different homopurine-homopyrimidine DNA tracts on hTERT promoter was based on their chromatin organization and is supported by a number of researches both in vitro and in vivo, suggesting a decreased target accessibility to TFOs in the nucleosomal environment [29][30][31].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The selection between different homopurine-homopyrimidine DNA tracts on hTERT promoter was based on their chromatin organization and is supported by a number of researches both in vitro and in vivo, suggesting a decreased target accessibility to TFOs in the nucleosomal environment [29][30][31].…”
Section: Discussionmentioning
confidence: 97%
“…The single stranded TFO 13 and TFO 18 and the two strands forming DNA 30 and DNA 18 ( Figure 1b) were synthesized on a 15 μmol scale via the phosphoramidite method, using a PERSEPTIVE Biosystems synthesizer, purified by ionic exchange High Performance Liquid Chromatography (HPLC) and successively desalted by molecular exclusion chromatography (Biogel P-2 fine). The purity was checked by reverse phase HPLC and electrophoresis in 20% denaturing polyacrylamide gel containing 7 M urea.…”
Section: Oligonucleotides Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these studies, triplex formation with DNA in native chromatin structure was not unambiguous confirmed. In addition, some in vitro experiments indicate that chromatin structure is incompatible with triplex formation (356,394,395). Therefore, to clarify the accessibility of target sites in the context of chromatin is crucial for developing antigene strategies.…”
Section: 33mentioning
confidence: 99%
“…These final 16 bp, however, were not sufficient for full initiation activity of an ori-beta mutant lacking the preceding repetitive sequences ( Figure 2D, 0.5DNR2 mutant). GA repeats have been shown to impede replication forks [37,47,48] and affect the assembly of DNA into nucleosomes [49], so both of these potential roles were investigated separately ( Figure 3). Importantly, a replication fork barrier (SB2) and an element that contains a nucleosomepositioning element (5S rDNA) were each able to independently replace the function of DNR ( Figure 3C).…”
Section: Transcription Factor Binding Sites Can Functionally Substitumentioning
confidence: 99%